Implementing Horizon Scanning as a tool for the strategic development of regulatory guidelines for nanotechnology-enabled health products - Rodríguez-Gómez, Francisco D.; Monferrer, Dominique; Penon, Oriol; Rivera-Gil, Pilar (Frontiers in Medicine, 2024)
Strategic regulatory development is essential to ensure that new innovations in nanotechnology-enabled health products (NHPs) successfully reach the market and benefit patients. Currently, the lack of specific regulatory guidelines for NHPs is considered one of the primary causes of the so-called “valley of death” in these products, impacting both current and future advancements. In this study, we have implemented a methodology to anticipate key trends in NHP development and compare them with the current regulatory landscape applicable to NHPs. This methodology relies on Horizon Scanning, a tool commonly used by policymakers to foresee future needs and proactively shape a regulatory framework tailored to those needs. Through the application of this methodology, different trends in NHP have been identified, notably NHPs for drug delivery and dental applications. Furthermore, the most disruptive elements involve NHPs that are multicomposite and multifunctional, harnessing nano-scale properties to combine therapeutic and diagnostic purposes within a single product. When compared with the regulatory landscape, current regulations are gradually adapting to accommodate emerging trends, with specific guidelines being developed. However, for the most disruptive elements, multicomposite and multifunctional NHPs, their novelty still poses significant regulatory challenges, requiring a strategic development of guidelines by regulatory agencies to ensure their safe and effective integration into healthcare practices. This study underscores the importance of proactive regulatory planning to bridge the gap between NHP innovation and market implementation.